Pengaruh Waktu Sentrifugasi pada Sexing Spermatozoa dengan Media Bovine Serum Albumin (BSA) Terhadap Motilitas dan Viabilitas Spermatozoa X-Y Sapi Simmental - PriyantoPriyanto, Langgeng; Riswandi, Riswandi; Setianingsih, Eva; Dwi Putranti, Oktora; Gunawan, Muhammad; Susanda, Apriansyah (Cannarium, 2022)
This study aimed to determine the effect of centrifugation time on sexing spermatozoa with Bovine Serum Albumin (BSA) media toward the motility and viability of spermatozoa X-Y Simmental cow. This research was carried out from October to November 2021 at the Sembawa Banyuasin Animal Feed Breeding Center, South Sumatra and the Animal Reproduction and Health Laboratory. Sample from Simmental type of cow semen the age 3 years. This study used 3 treatments with 4 repetitions. The observed variables were the motility and viability values of Simmental cattle spermatozoa. Data were analyzed using ANOVA and Duncan's test 5%. The results showed that the with a centrifugation time of 4 minutes(P1) with a speed of 1500 rpm got the best results for the motility value of spermatozoa X = 61.54% and spermatozoa Y = 56.71%, the best value of spermatozoa viability X = 66.17 and spermatozoa viability Y = 62, 46%. It can be concluded that the longer the centrifugation time can affect the quality of the spermatozoa which results in a decrease in the motility and viability of the spermatozoa X-Y Simmental Cow.Ã‚Â Keywords: Sexing, Bovine Serum Albumin, Centrifugation, Motility and viability